On Certain Values and Anti-Values in Russian and Lithuanian Communicative Cultures - Лихачева, Алла (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] This article explores certain features of the Russian and Lithuanian communicative cultures and analyzes the opposite – from the axiological perspective – communicative manifestations in each of the compared cultures. The comparison of Russian and Lithuanian communicative cultures shows that both communicative cultures are contradictory, and that the national characters of the representatives of these cultures combine paradoxical features. Communicative values t hat are usually assigned to Russians are openness, close contact, cordiality, emotionality, but these are accompanied by harshness, assertiveness, an aspiration to correct another’s behavior and a lack of tolerance. Lithuanians value the following communicative qualities: moderateness, kindliness, friendliness and a compliance to the standards of decency, but they acknowledge their communicative closedness, jealousy, pessimism, mistrust. Discrepancies between the reflexive communicative categories (which are understood to represent the ideal or norm) and those found in everyday life (which reflect how things are in real communication) make obvious the difference between the values a nd antivalues in both communicative cultures.